Performance Testing of Cordless Handheld Vacuum Cleaners - Jason Lin; Yu-Mei Kuo; Maxie Lin; Cindy Lin; Pei-Yao Tsai; Chih-Wei Lin; Sheng-Hsiu Huang; Chih-Chieh Chen (Aerosol and Air Quality Research)
Abstract The cordless handheld vacuum cleaner (CHVC) is a compact variation of the full-sized vacuum cleaner designed to remove dust and dirt in tight, indoor spaces such as cars and under stairwells. Vacuum cleaning activities generate and re-suspend particulate matter (PM) within enclosed spaces, raising concerns regarding indoor air quality. Despite growing popularity and known health risks associated with elevated PM concentration, there is limited research regarding aerosol emission from CHVCs. Our study aimed to investigate PM emission from CHVC and identify the key contributing factors. Two custom-built test systems were designed to quantify the suction pressure and aerosol penetration of the filter cartridge. We tested six popular CHVC models under different conditions and found that filter cartridge sealing, motor design, and dust load can affect PM emissions. Brushed motors emit more particles than brushless motors and interfere with the filter performance. We also found that some filter cartridges did not tightly seal the filter to the housing, significantly increasing PM emission especially as more dust collects on the filter media. While leaky cartridges might result in higher suction and clean air delivery rates at the same power, we still recommend guidelines for airtight filter cartridge design due to the risk posed by elevated PM emissions. Our findings also suggest the need for guidelines concerning motor assembly, motor type, and design standards. For immediate mitigation, users should ventilate areas and use respiratory protection.